Finite Element Analysis and Electrohydrodynamic Multiphysics Modeling of a Corona-Streamer Discharge in a Two-Phase Flow Medium - Myung-Ki Baek; Ho-Young Lee (Energies)
This study proposes an electrohydrodynamic multiphysics modeling and finite element analysis technique to accurately simulate corona-streamer discharges in a two-phase flow medium. The discharge phenomenon is modeled as a multiphysics system, coupling the Poisson equation for the electric field with a charge dynamics model based on fluid methods and a thermofluid field for temperature effects. To optimize the numerical simulation, the tip-flat plate electrode model was simplified to two-dimensional axisymmetry, and an unordered lattice network was used to reduce computational time while maintaining high resolution in the region of interest. A high DC voltage was applied to the model to generate a local non-uniform electric field exceeding 10 MV/m, allowing the numerical simulations of ionization, recombination, and charge attachment in the streamer channel. The numerical results were compared with voltage and current measurements from full-scale experiments under identical geometry and initial conditions to verify the effectiveness of the proposed method. The results of this study enhance the understanding of the multiphysical mechanisms behind electrical discharge phenomena and can enable the prediction of insulation failure through simple simulations, eliminating insulation experiments on devices.